Adults with spinal muscular atrophy: a large-scale natural history study shows gender effect on disease. Issue 12 (11th October 2022) - Maggi, Lorenzo; Bello, Luca; Bonanno, Silvia; Govoni, Alessandra; Caponnetto, Claudia; Passamano, Luigia; Grandis, Marina; Trojsi, Francesca; Cerri, Federica; Gardani, Alice; Ferraro, Manfredi; Gadaleta, Giulio; et al.
Abstract : Background: Natural history of spinal muscular atrophy (SMA) in adult age has not been fully elucidated yet, including factors predicting disease progression and response to treatments. Aim of this retrospective, cross-sectional study, is to investigate motor function across different ages, disease patterns and gender in adult SMA untreated patients. Methods: Inclusion criteria were as follows: (1) clinical and molecular diagnosis of SMA2, SMA3 or SMA4 and (2) clinical assessments performed in adult age (>18 years). Results: We included 64 (38.8%) females and 101 (61.2%) males (p=0.0025), among which 21 (12.7%) SMA2, 141 (85.5%) SMA3 and 3 (1.8%) SMA4. Ratio of sitters/walkers within the SMA3 subgroup was significantly (p=0.016) higher in males (46/38) than in females (19/38). Median age at onset was significantly (p=0.0071) earlier in females (3 years; range 0–16) than in males (4 years; range 0.3–28), especially in patients carrying 4 SMN2 copies. Median Hammersmith Functional Rating Scale Expanded scores were significantly (p=0.0040) lower in males (16, range 0–64) than in females (40, range 0–62); median revised upper limb module scores were not significantly (p=0.059) different between males (24, 0-38) and females (33, range 0–38), although a trend towards worse performance in males was observed. In SMA3 patients carrying three or four SMN2 copies, an effect of female sex in prolonging ambulation was statistically significant (p=0.034). Conclusions: Our data showed a relevant gender effect on SMA motor function with higher disease severity in males especially in the young adult age and in SMA3 patients.